Effects of foliar fertilization of common bean (Phaseolus vulgaris, L.) during the seed-filling stage - Neptune, A.M.L.; Muraoka, T. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1977)
An experiment was carried out with common bean (Phaseolus vulgaris, L.) in a Red Yellow Latossol, sandy phase, in order to study the influence of foliar spraying of the Hanway nutrient solution (NPKS) at grain filling stage on: 1) grain yield; 2) the uptake of fertilizer and soil nitrogen by this crop through the root system and 3) the efficiency of utilization of the nitrogen in the foliar spray solution by the grain. The results of this experiment showed that the foliar application of the Hanway solution with ammonium nitrate at the pod filling period caused severe leaf burn and grain yield was inferior to that of the plants which received a soil application of this fertilizer at the same stage. These facts can be attributed to the presence of ammonium nitrate in the concentration used. The composition of final spray was: 114,28 Kg NH4NO3 + 43,11 Kg potassium poliphosphate + 12,44 Kg potassium sulphate per 500 litres. The uptake of nitrogen fertilizer through the root system and the efficiency of its utilization was greater than that through the leaves.